The Quality Criteria of Oriental Tobacco Leaves Grown Under Dry Farming. - J, Mohamad Ali J. (Sulaimani Journal for Pure and Applied Sciences, 1997)
A field experiment in split plot design was carried out to evaluate the oriental tobacco leaves, cultivar Gullsor grown under dry farming at Sulaimani Region. The results indicated that the quality of tobacco grown with both mulching and non-mulching were acceptable under dry farming in terms of chemical constituents such as reducing sugar, total alkaloide, and chlorine and some physical properties including leaf dimentions, specific surface area, leaf density, filling value and equilibrium moisture content.